Analisis Penerapan Tarif Jasa Antar Bahan Bakar Minyak (BBM) Solar Industri pada PT Citra Lestari Sejahtera (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
Conditions of business development is advancing rapidly lead to the level of competition is growing sharply so in the operations the company continues to face various problems, one of which is how to set the price is right so that the items offered may be sold or otherwise how to attract consumers to buy goods on offer. Companies generally aim to increase profits, to be able to sustain its business and expand its business. With large profits companies can make up their own capital increase. The amount of profit is determined by substantial costs and sales. To get great profits need to increase efficiency and sales volume.